Numerical and experimental study of a novel compact micro fluidized beds reactor for CO2 capture in HVAC - Wang, Lei (2016)
In order to reduce the pressure drop and increase the adsorption performance for the CO2 capture using solid adsorbents in Heating, Ventilation and Air Conditioning (HVAC), a novel Compact Micro Fluidized Beds (CMFB) reactor was proposed. First, the pressure drop and adsorbent attrition of the CMFB reactor were calculated by Eulerian-Lagrangian Computational Particle-Fluid Dynamics (CPFD) modelling with Barracuda software and compared with traditional Fluidized Bed (FB) reactor. Second, a CMFB experimental platform was designed based on the CPFD model. At last, the pressure drop, adsorbent attrition and performance for CO2 capture were systematically investigated in the CMFB experimental platform. The results showed that much lower pressure drop and lower adsorbent attrition were achieved by CMFB reactor than by FB reactor due to large inlet area and reduced feed velocity. The CMFB reactor can gain long-term energy-saving effects in HVAC. Furthermore, the breakthrough time increased by about 35% and the saturation time reduced by about 17% in CMFB reactor for CO2 capture than that in FB reactor.